REPATRIATION ADJUSTMENT AND KNOWLEDGE SHARING: A THEORETICAL VIEW - Yogeswaran, T.; Vijayakumar, R.; Balasubramaniam, J.; James, R. (University of Jaffna, 2017)
International human resource management (IHRM) literature widely discusses the issues of repatriation of employees in multinational companies. This literature mainly focuses on job related variables and provides theoretical models for repatriation adjustment of corporate employees. However, these models are not sufficient to understand the repatriation process of other repatriates working in different types of organizations. Thus, this study focuses on developing a model that explains causes and consequences of repatriation adjustment of all types of business employees based on existing relevant literature and theories in different field of study. The proposed model was supported by Uncertainty reduction theory socialization tactics theory and cognitive and sense making theory. This model suggests that individual, group and organizational level strategies need to be developed to facilitate repatriation adjustment and the successful repatriation adjustment encourages employees’ knowledge sharing intention. Further, it discusses the role of repatriates’ personal and situational variables on adjustment. This study contributes to the literature in a way of providing a meaningful theoretical model explaining the factors that facilitate repatriation adjustment and its consequences, and relates socialization theories to repatriation adjustment. This study highlights the role of individual, group and organization in the process of repatriation adjustment and improved (better) use of top talent at the organization.
Keywords: adjustment; coworker; knowledge sharing; repatriation